Primates in zoo stressed by the absence of visitors: A model provided by the covid-19 pandemic - Froylán Albarrán Tamayo; J. J. Barroso Padilla; M. A. Carpio Valdivia; A. E. Sandoval Higareda; Bernardo Bañuelos Hernández; Andrés Cruz Hernández (Nova Scientia)
The stress suffered by other animal species has not been considered in many situations of interaction with humans. Captive animals in zoos have constant interactions with their keepers, their doctors and with visitors. The objective of our study was to better understand the influence of visitors on the stress of captive animals. Like others around the world, the Zoo in Leon, Guanajuato, Mexico, closed its doors to visitors during the COVID-19 pandemic. We took advantage of this period to measure hair cortisol in mammals after months without visitors and months after visitors returned. Samples were taken whenever there was an opportunity for handling. Our results did not show a significant difference when considering all specimens sampled, however, we found that primates were significantly more stressed in the absence of visitors, as opposed to the rest of the animals who showed more stress with the presence of visitors, although not significantly. This supports the hypothesis that some animals have an adaptation to the presence of the public and even, in the case of primates, interaction with humans could become a beneficial factor.